Modelo pedagógico para la formación de los docentes de matemáticas de la educación básica primaria usando como herramienta el laboratorio de matemáticas - Romero Huertas, Alfonso (Universidad Antonio Nariño, 2023)
The purpose of this research was to build a continuous training model for practicing teachers at the basic primary education level who work in the area of mathematics in the Department of Cundinamarca’s schools, using the laboratory as a tool through which is strengthened the disciplinary and pedagogical knowledge of the content in the area in question.